IMPLEMENTATION OF CURRICULUM BASED ON KKNI VOCATIONAL HIGHER EDUCATION TO IMPROVE COMPETENCE PROFESSIONAL GRADUATES - Dadang Kusmayadi; Iim Wasliman; Yosal Iriantara; Sri Handayani (IJGIE (International Journal of Graduate of Islamic Education), 2022)
Problems in terms of the curriculum are still found, including in the Diploma Three Study Program. This problem occurs in the dimensions of curriculum implementation, namely the gap between the curriculum as a form of document and the curriculum as a process. This means that the curriculum in the form of a syllabus contained in the standard content document has not been carried out properly in learning activities. This research uses a qualitative approach with case study methods and data collection techniques through interviews, observations, and document studies. The results of this study indicate that: (1) The stages of curriculum implementation in the D III Nursing Study Program, namely: the formulation of curriculum objectives, the basis for curriculum design and development, curriculum organization and structure, learning strategies and methods, professional ability development, scheduling of lecture activities, elements of supporting elements, development systems, evaluation of the curriculum process; (2) Internal constraints include human resources, finance, raw input, learning facilities and strategies. Externally, the policy and development of science is so fast; (3) Solutions to internal obstacles, namely professional development of educators and education staff, effectiveness and efficiency of internal financial sources, optimization of student development through academic supervisory lecturers, procurement of goods according to priority scale. External solutions, namely, intense communication with stakeholders.